Preterm Birth in Georgia. Analysis Based on the Data of “Georgian Birth Registry” - Kvaratskhelia, Natia; Tkeshelashvili, Vasil (Caucasus Journal of Health Sciences and Public Health, 2020)
Preterm birth is the main cause for illness and death and is a global issue for public health. In spite of acute need, effective guidelines on assessing risks for preterm birth and prevention of associated complications are still not in place. Regardless of the improved quality of prenatal care, prevalence of preterm birth among liveborn babies in 2019 is quite high in Georgia (8.1%) compared to other countries. Guidelines for preventive methods and management for Georgian population are based on non-Georgian experience, due to lack of national population research.